Anti-Inflammatory Effect of Acetone Extracts from Microalgae Chlorella sp. WZ13 on RAW264.7 Cells and TPA-induced Ear Edema in Mice - Yang, Longhe; Hu, Fan; Yan, Yajun; Yu, Siyu; Chen, Tingting; Wang, Zhaokai (Frontiers in Marine Science, 2022)
Microalgae extracts have a wide range of uses in the field of healthcare and nutrition. However, the use of microalgae extracts in anti-inflammatory properties and their mechanism of action have not yet been fully studied. Here, we show that extracts from Chlorella sp. WZ13 (CSE-WZ13) dose-dependently reduced nitrite production, inhibited the expression of inducible nitric oxide synthase (iNOS) protein, and decreased the production of the gene and inflammatory cytokines tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6), in lipopolysaccharide (LPS)-stimulated RAW264.7 cells. Using high-content imaging analysis, it was found that CSE-WZ13 inhibited the translocation of nuclear factor kappa B (NF-κB) from the cytoplasm to the nucleus. CSE-WZ13 also exerted anti-inflammatory effects in an ear edema mouse model induced by 12-O-tetradecanoylphorbol-13-acetate (TPA). CSE-WZ13 inhibited edema by 36.17% and 25.66% at a dose of 0.3 and 0.1 mg/ear, respectively. Histological analysis showed that topical application of CSE-WZ13 decreased TPA-induced inflammatory cell infiltration. Our results indicate that CSE-WZ13 may be a useful candidate for the purpose of decreasing inflammation.